2015
DOI: 10.1158/0008-5472.can-14-1996
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Pharmacologic Inhibition of eIF4E Reduces Breast Cancer Cell Migration, Invasion, and Metastasis

Abstract: The translation initiation factor eIF4E is an oncogene that is commonly overexpressed in primary breast cancers and metastases. In this article, we report that a pharmacologic inhibitor of eIF4E function, ribavirin, safely and potently suppresses breast tumor formation. Ribavirin administration blocked the growth of primary breast tumors in several murine models and reduced the development of lung metastases in an invasive model. Mechanistically, eIF4E silencing or blockade reduced the invasiveness and metasta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 46 publications
4
84
1
Order By: Relevance
“…Our findings contrast with a recent report demonstrating that targeting eIF4E in breast cancer cells inhibited TGF-β-induced vimentin and Snail expression (44). We show that the effect of eIF4E on ZEB1 levels in PDAC cells is through its effect on miR-200c and miR-141 microRNAs.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings contrast with a recent report demonstrating that targeting eIF4E in breast cancer cells inhibited TGF-β-induced vimentin and Snail expression (44). We show that the effect of eIF4E on ZEB1 levels in PDAC cells is through its effect on miR-200c and miR-141 microRNAs.…”
Section: Discussioncontrasting
confidence: 99%
“…This O-glycosylation is thought to act in a manner analogous to phosphorylation [20, 21]. In support of these findings, recent clinical studies have demonstrated a close correlation between MMP-3 expression and the development of lung metastases in breast and lung cancers [22, 23]. In our study, which analized the expression of three MMPs, we found that glucosamine sulfate treatment exerted an unexpectedly specific effect.…”
Section: Discussionsupporting
confidence: 87%
“…19,20 Here, we show that TEHsp90 controls posttranscriptional dynamics of key mRNA species including those encoding BCL6, MYC, and BCL2 in DH/TH DLBCLs. We identify that eIF4E simultaneously modulates the mRNA export and translation of these genes and that TEHsp90 modulates eIF4E activity.…”
Section: Introductionmentioning
confidence: 75%